Analisis manajemen risiko pembiayaan pada perbankan syariah: Identifikasi risiko, faktor penyebab, serta strategi penanganan pembiayaan bermasalah dalam perspektif kajian pustaka - Octavia, Irene Hevy (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze financing risk management in Islamic banking, focusing on risk identification, the factors causing problematic financing, and strategies for handling and resolving them. The method used in this study was a literature review, examining various journal sources related to risk management and Islamic financing. The results indicate that financing risk is a primary risk in Islamic banking activities, arising from the inability of customers to meet their obligations. Problematic financing is caused by internal bank factors, customer factors, and external conditions such as the economy and government policies. Therefore, comprehensive risk management is required through the stages of risk identification, measurement, monitoring, and control. Furthermore, preventative measures are implemented through financing feasibility analysis, the application of prudential principles, and ongoing supervision. Problematic financing is handled through financing restructuring, such as rescheduling, reconditioning, and restructuring, as well as other resolution measures. With the implementation of effective risk management, Islamic banks are expected to minimize losses and maintain sustainable financial stability.